KINERJA PEGAWAI DALAM LAYANAN PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN SIDENRENG RAPPANG - Muhammad Nur; Andi Nilwana; Irwin Hatibu; Barisan Barisan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to analyze the performance of the employees of the Transportation Service Office of Sidenreng Rappang district in motor vehicle testing services and to analyze the factors that influence employee performance in testing motorized vehicles. This study uses a qualitative approach, data collection using interview techniques, observation and documentation. Determination of samples/informants using purposive sampling technique while processing and analyzing data using the Nvivo 12 application. The results showed that the performance of employees in motor vehicle testing services was assessed based on performance indicators of quantity, quality, effectiveness, independence and work commitment in general good. The effectiveness indicator is considered still lacking in terms of the time required for testing for each vehicle beyond the targeted time. Factors that affect employee performance in vehicle testing include organizational structure, human and financial resources. Financial factors are still lacking so that it becomes an obstacle in optimizing employee performance. The findings of this study also reveal that the decline in the number of vehicles tested during the last three years is influenced by external factors, namely the low awareness of some people to register for vehicle testing.